Segregation and potential functional impact of a rare stop-gain PABPC4L variant in familial atypical parkinsonism - Aslam, Muhammad; Eils, Roland; Schlesner, Matthias (Scientific reports, 2019)
Atypical parkinsonian disorders (APDs) comprise a group of neurodegenerative diseases with heterogeneous clinical and pathological features. Most APDs are sporadic, but rare familial forms have also been reported. Epidemiological and post-mortem studies associated APDs with oxidative stress and cellular protein aggregates. Identifying molecular mechanisms that translate stress into toxic protein aggregation and neurodegeneration in APDs is an active area of research. Recently, ribonucleic acid (RNA) stress granule (SG) pathways were discussed to be pathogenically relevant in several neurodegenerative disorders including APDs. Using whole genome sequencing, mRNA expression analysis, transfection assays and cell imaging, we investigated the genetic and molecular basis of a familial neurodegenerative atypical parkinsonian disorder. We investigated a family with six living members in two generations exhibiting clinical symptoms consistent with atypical parkinsonism. Two affected family members suffered from parkinsonism that was associated with ataxia. Magnetic resonance imaging (MRI) of these patients showed brainstem and cerebellar atrophy. Whole genome sequencing identified a heterozygous stop-gain variant (c.C811T; p.R271X) in the Poly(A) binding protein, cytoplasmic 4-like (PABPC4L) gene, which co-segregated with the disease in the family. In situ hybridization showed that the murine pabpc4l is expressed in several brain regions and in particular in the cerebellum and brainstem. To determine the functional impact of the stop-gain variant in the PABPC4L gene, we investigated the subcellular localization of PABPC4L in heterologous cells. Wild-type PABPC4L protein localized predominantly to the cell nucleus, in contrast to the truncated protein encoded by the stop-gain variant p.R271X, which was found homogeneously throughout the cell. Interestingly, the wild-type, but not the truncated protein localized to RasGAP SH3 domain Binding Protein (G3BP)-labeled cytoplasmic granules in response to oxidative stress induction. This suggests that the PABPC4L variant alters intracellular distribution and possibly the stress granule associated function of the protein, which may underlie APD in this family. In conclusion, we present genetic and molecular evidence supporting the role of a stop-gain PABPC4L variant in a rare familial APD. Our data shows that the variant results in cellular mislocalization and inability of the protein to associate with stress granules.
Gesehen am 05.12.2019